2002
DOI: 10.1046/j.1365-3180.2002.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical period of weed control in transplanted chilli pepper

Abstract: Summary Field experiments were conducted from 1991 to 1993 to determine the critical period of weed control in chilli pepper. The maximum weed‐infested period ranged between 0.7 and 3.2 weeks after transplanting (WAT) at a 5% yield loss level. To prevent losses in total and marketable yields, weeds should be removed 2.1 or 0.9 WAT respectively. The end of the critical period decreased as the predetermined yield loss level increased from 2.5% to 10%. The minimum weed‐free period ranged between 6.7 and 15.3 WAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 19 publications
2
23
0
2
Order By: Relevance
“…The data on weed biomass support this conclusion (Figs 1 and 2). Ghosheh and colleagues (1996) pointed out that long critical periods are indicative of more competitive crops (Amador‐Ramirez, 2002). However, it must be remembered that in the experiments reported in this paper, weed emergence may have been delayed by the use of trifluralin as a pre‐planting treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data on weed biomass support this conclusion (Figs 1 and 2). Ghosheh and colleagues (1996) pointed out that long critical periods are indicative of more competitive crops (Amador‐Ramirez, 2002). However, it must be remembered that in the experiments reported in this paper, weed emergence may have been delayed by the use of trifluralin as a pre‐planting treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The development of an Integrated Weed Management System (IWM) requires knowledge of the behaviour of weeds in the agro‐ecosystem, including possible effects on crop yield (Amador‐Ramirez, 2002). The critical period of weed control is a key component of strategies for IWM and the results of the experiments contribute to the development of such a system for Turkish cotton growers.…”
Section: Discussionmentioning
confidence: 99%
“…The lower tuber yield in 2011 can be attributed to the higher weed density compared with 2010. Decrease in crop performance with increasing duration of weed interference has been reported by some researchers working on potato (Thakral et al 1989;Ahmadvand et al 2009) and other crops (Amador-Ramirez 2002;Bukun 2004;Mohammadi et al 2004). Yield responses and critical period of weed control Since a significant interaction between year and weed competition levels was observed (data not shown), relative data were not pooled across the year.…”
Section: Resultsmentioning
confidence: 96%
“…Results of the experiments showed that the yield of pepper significantly declined with increasing duration of weed presence and this response was in agreement with previous findings reported on other crops (Van Acker et al . 1993; Medina 1995; Amador–Ramirez 2002; Bukun 2004; Arslan et al . 2006; Tursun et al .…”
Section: Resultsmentioning
confidence: 99%
“…Although many studies have been conducted to determine the CPWC in various crops under various environmental conditions, there are a limited number of studies on the critical period for weed control in vegetables in general and pepper in particular (Weaver 1984; Baumann et al . 2000; Amador–Ramirez 2002; Tursun et al . 2004, 2007; Buckelew et al .…”
mentioning
confidence: 99%